Effects of transverse oscillation on tensile properties of mild steel weldments - Tewari S.P. (My University, 2025)
In this paper an attempt has been made to study the effects of frequency and amplitude of transverse oscillation on yield strength, ultimate tensile strength, breaking strength and percentage of elongation of weldments. The weldments were prepared under different oscillatory conditions. The frequency and amplitude of transverse oscillations during experimentation were varied from 0 to 400 Hz and 0 to 40 μm respectively. The tensile properties of the weldments prepared under oscillatory conditions are improved whereas the percentage of elongation reduced when compared with the stationary welded test specimens. It has been observed that increase in frequency of transverse oscillation results in the improved tensile properties of the weldments except the percentage of elongation which decreases with increase in frequency of oscillation. At 80 Hz frequency higher amplitude show greater value of tensile strength than lower amplitude. But at higher frequencies (300 Hz and 400 Hz) lower amplitudes show a significant increase in tensile strength value than higher amplitudes. The increase in tensile strength under oscillatory condition is due to the grain refinement which is caused by dendrite fragmentation and grain detachment mechanism.